Analisis Aliran Fluida Dua Fase (Udara-Air) melalui Belokan 45o - Awaluddin, Awaluddin; Wahyudi, Slamet; Widodo, Agung Sugeng (Jurnal Rekayasa Mesin, 2014)
The phenomenon of two phase flow can be foundin our nature, at the living bodyand industrial of the world. The flow of Fluid throughthe pipe bendshave a valuegreater than thepressure dropstraight pipeitâ€™s was because the changes ingeometryandtrajectorythathave an impact onthe changeof flowpattern. This research aims to determine of theflowpatternandtwo-phase flowpressure dropthat occursthrough the 45Â° elbowfrom the horizontalto theverticalslopes upward. Diameter ofthepipe(D) 26.64mm, variationsthatdoaregasflow rate(Q ) (1 - 3) LPMandgasvolumefraction (Î²) (25 - 50) %. From theresults ofthis research we can concludedthat theflowpattern thatoccursisthe slug/plugflowwhere the greaterthe gasvolumefraction (Î²), the size of theslug/plugflowgreaterandinversely proportional to thepressure dropfurtherdown. Upheaval of two-phase flow patterns due to the influence of gravity occurs at the actual speed ratio of air and water (v ) at 1 LPM air 0.713 and 0.966 at 3 LPM air. The highestpressure dropoccurswiththe condition ofthe gasvolumefraction (Î²) of 50 %, actual speed ratio of air and water(v G /v L ) 0.764at107.415 Pa in theoretically and 214.616Paat experimentally.Keywords: 45 o elbow, flow pattern, pressure drop.